ChemInform Abstract: Magnetic Properties and Magnetocaloric Effect in Ternary REAgAl (RE: Er and Ho) Intermetallic Compounds. Issue 52 (29th December 2014) - Zhang, Yikun; Yang, Baijun; Wilde, Gerhard
Abstract The intermetallics of title are prepared by arc melting of the elements and subsequent annealing (evacuated quartz tubes, 873 K, 72 h).